Pelatihan Mindfulness untuk Meningkatkan Kesejahteraan Psikologis Remaja Difabel Fisik - Arum Sukma Kinasih; M. Noor Rochman Hadjam (Universitas Islam Indonesia, 2011)
Physical differential ability adolescents have difficulty to develop their potential so imply their psychological welibeing. The aim of this research was to examine the effect of mindfulness training to increase psychological welibeing of physical differential ability adolescents. The pretest-posttest experimental design were used in this research. Participants were 5 male clients stay at physically differential abibility rehabilitation center, 18-24 years old and got physical diferential ability cause by accident and illness. Results showed that mindfulness training was not significantly effective to increased psychological welibeing to participants. From pretest to posttest showed that z=-1.841 and p=0.06 (p< 0.05). From posttest to follow up showed that z=-0.135 dan p^O.893 (p<0.05). Qualitative abalysis showed that subject's psychological welibeing scale score lower than pretest because they didn't practice mindfulness regularly and feel anxious with the future. One subject got higher psychological welibeing scale score than pretest because practice mindfulness regularly, high motivation and proactive in mindfulness training process. For the future research should consider about mindfulness training time, evaluation and debriefing processKey Word; Physical differential ability adolescents, Mindfulness training, Psychological welibeing